Konstruksi Gaya Hidup Minimalis Pekerja SCBD di Media Sosial (Studi Netnografi Pada Akun Tiktok @Budakcorporate): (Studi Netnografi Pada Akun Tiktok @Budakcorporate) - Agstia Esa Handayani; Fajar Hariyanto; Weni Adityasning Arindawati; Khairul Arief Rahman (JIKE: Jurnal Ilmu Komunikasi Efek, 2024)
The emergence of a minimalist lifestyle in Indonesia has become increasingly popular in recent years. This research was conducted with the aim of analyzing the construction of a minimalist lifestyle and how to build an image as an SCBD worker in video content uploaded by the tiktok account @budakcorporate. The use of qualitative methods with a netnographic approach was carried out in July-December 2022. The minimalist lifestyle is basically a trend that aims to suppress consumerism. However, the content uploaded by the Tiktok account @budakcorporate shows that a minimalist lifestyle still involves consumerism depending on what the individual or perpetrator emphasizes. The implication is that there is a shift in the meaning of the minimalist lifestyle definition itself, from a concept of simplicity to a lifestyle that leans towards consumerist values.